Magma mixing in the Karamaili granite belt of Eastern Junggar: evidence from A2-type granites and their mafic microgranular enclaves - Sun, Yafei; Zhang, Bowen; Yao, Yuan; Zhan, Xinzhong; Yalikun, Yaxiaer; Wang, Yacong (Frontiers in Earth Science, 2025)
The Karamaili Orogenic Belt forms an essential part of the southernmost margin of the Eastern Junggar Orogenic Belt. The Late Carboniferous granitic belt of the Karamaili belt provides a valuable natural setting for studying the evolution of silicic magmas. In this study the petrology, rock geochemistry, and chronology of granite and mafic microgranular enclaves (MMEs) in the Sabei, Huangyangshan, and Sujiquan plutons are investigated. The results show similar zircon U-Pb ages of 315.9 ± 2.4 Ma, 316.1 ± 2.2 Ma, 319.4 ± 2.0 Ma, and 313.9 ± 3.5 Ma for the granite and Sabei MMEs. The granites are high silica, alkali-rich, weakly alkaline to sub-aluminous A2-type, and are strongly depleted in Eu. They are enriched in Ta, Th, U, Rb, K, and Pb, and formed in a post-collisional extensional environment. In contrast, the Sabei MMEs are sub-aluminous, calc-alkaline to high-K calc-alkaline gabbroic enclaves that exhibit typical magmatic structures and evidence of mixing and evolution. They represent residual dioritic enclaves derived from underplated, rising mafic magma that underwent mixing. Whole-rock εNd(t) values of +4.0 to +4.5 for the Sabei, Huangyangshan, and Sujiquan plutons, and εNd(t) values of +5.5 to +5.7 for the Sabei MMEs, indicate the involvement of juvenile mantle-derived magmas, suggesting significant juvenile crustal growth in the region. The results reveal intense mafic magmatism associated with the Karamaili granites. It included mafic magma input that generated highly differentiated granites, such as the Kamusite granite and mafic magmatic components contributing to eastern plutons and forming alkaline granites rich in dioritic enclaves like the Sabei and Huangyangshan granites. This study provides petrogenetic constraints on the formation of plutons in the Karamaili Granite Belt and the evolution of siliceous magmas in the region.